Age matters: how demographics influence visitor perception and attitude at the destination level. (2017) - Li, Jun; Ali, Faizan; Kim, Woo Gon
The competitiveness of tourist attractions depends on satisfying visitors, saving money, and achieving revisits. Therefore, it is very important to know the roles of visitors' awareness of their satisfaction, theoretical relationships, and loyalty to a destination in both theoretical and empirical aspects. In most of the previous empirical research related to the relationships among destination images, visitors' satisfaction, and their behavioural intentions to a destination, the moderating variables were not considered. Therefore, in this study, we analyse the moderating effects of certain personal features of different age groups on the theoretical relationship among visitors' satisfaction and their behavioural intentions to a destination and that destination's image. More specially, this research is conducted based on the exploration of the influences of differences in ages on the relationships between the destination's image and the visitors' satisfaction or behavioural intentions. Based on the multiple-group causes and effect analyses, the research results show that the visitors' personal features significantly affect the relationship between the destination's image and visitors' satisfaction or behavioural intentions. Moreover, in general, these relationships tend to be stronger for younger visitors. Finally, the influences are analysed and discussed in both the theoretical and practical aspects.